Cytochalasins D1 and C1, unique cytochalasans from endophytic fungus Xylaria cf. curta. Issue 34 (22nd August 2019) - Wang, Wen-Xuan; Feng, Tao; Li, Zheng-Hui; Li, Jing; Ai, Hong-Lian; Liu, Ji-Kai
Graphical abstract: Highlights: Two cytochalasans with oxygen bridged macrocycle identified from endophytic Xylaria cf. curta . Their structures were determined by 1D/2D NMR, ECD calculation and GIAO 13 C NMR calculation. They showed moderate cytotoxicity against human leukemia cell line HL-60. Abstract: Cytochalasins D1 (1 ) and C1 (2 ) were isolated from the liquid fermentation of fungus Xylaria cf. curta . Their structures and absolute configurations were determined by comprehensive experimental spectroscopic methods as well as ECD and GIAO 13 C NMR calculation. They possess a unique eleven-membered macrocycle with an oxygen bridge. Cytochalasins D1 and C1 showed moderate cytotoxicity against human leukemia cell lines HL-60 with IC50 value of 12.7 and 22.3 μM, respectively.